Relationship between ethical and Islamic banking systems and its business management implications - T. A. Saidi (South African Journal of Business Management, 2009)
Islamic banking has become the fastest growing sector in the financial markets of the world in the past three decades, and this growth trajectory has coincided with the world's renewed interest in the ideas of ethical banking. This raises the question regarding the actual nature of the relationship between ethical and Islamic banking systems, and the analysis in the current paper intends to provide answers to this question. The analysis has shown that the practices of Islamic banking system fit into ethical banking framework to a greater extent. It concludes that Islamic banking forms part of the broad ethical banking brand, and thus its rapid growth at the time when the ethical banking movement gathers new momentum could not be a matter of sheer coincidence.The paper also examines three business management implications of its findings. One implication is that proper name selection is an important aspect of successful branding and marketing of products or services; and the second is that we are in the age of committed consumption whereby principles, ethics and image are Issues of importance in people's choice of brands. The third implication is that market niching business strategies could bring success if properly designed and executed.
Keywords: 650